Analyzing Frameworks for Green IT Adoption in Organizations: A Systematic Literature Review - Maulana Muhammad; Bayu Waspodo; Zahra Sabila Nugraha (Jurnal Informasi dan Teknologi, 2025)
Sustainability has emerged as a fundamental objective for organizations aiming to achieve the highest levels of maturity within various IT Governance Frameworks. Green IT has emerged as a concept aligned with the essence of organizational sustainability. Its primary challenge lies in the difficulty of integrating Green IT principles into the organization's business processes. Therefore, the framework employed plays a crucial role in facilitating the adoption of Green IT. This Systematic Literature Review uses Kitchenham to review various literature on the topic of Green IT adoption in organizations with a focus on their role in supporting sustainable behaviors. The review process shows the three primary frameworks, namely the Governance and Management Framework for Green IT (GMGIT), the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2), and the Green IT Maturity Model. The analysis indicates that these frameworks are primarily employed in the IT services and manufacturing sectors, highlighting their effectiveness in addressing environmental sustainability, carbon emissions, and energy consumption. Gaps remain, especially in the government sector, where Green IT principles are underexplored. The research identifies challenges in executing these frameworks, specifically the tendency to favor short-term adoption strategies over long-term sustainability objectives. To enhance the success of Green IT adoption, firms at maturity levels 1-3 must initially evaluate their preparedness prior to fully integrating Green IT principles into their business processes. This study provides comprehensive insights into the frameworks utilized for Green IT adoption, including substantial recommendations for future research and practical applications in emerging domains.